lifestyle and home - Lidin, Konstantin (project baikal, 2023)
Home is a special place where time flows in a very special way. At home, the walls help, and the past never dies. Home is my fortress and a place where I meet my loved ones. Home is both a protective cover facing the outside world and a reflection of the most personal, deep and secret recesses of the soul. In the section devoted to housing, we present the materials of two round tables held with young people in Novosibirsk and Irkutsk. How do representatives of the next generation imagine their home?They will tell us about it. The problem of co-housing was already solved a hundred years ago within the concept of Socialist City (and brought extremely controversial results), but today this theme is returning, while attracting the attention of architects and sociologists on a new digital design platform. Similarly, there is a renewed interest in traditional materials for residential housing, especially, wood. How to teach young architects of the “era of concrete, glass and metal” the skills of designing in wood? This section contains articles devoted to it.
Keywords: home; young people; residential housing